2019
DOI: 10.1101/574103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of MERS-CoV (Middle East Respiratory Syndrome Coronavirus) seroprevalence and viral RNA prevalence in dromedary camels: implications for animal vaccination

Abstract: 27Human infection with Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is driven by 28 recurring dromedary-to-human spill-over events, leading decision-makers to consider dromedary 29 vaccination. Dromedary vaccine candidates in the development pipeline are showing hopeful results, 30 but gaps in our understanding of the epidemiology of MERS-CoV in dromedaries must be addressed 31 to design and evaluate potential vaccination strategies. We systematically reviewed the published 32 literature reporting s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 78 publications
(134 reference statements)
1
2
0
Order By: Relevance
“…Younger camels in Kazakhstan had a higher probability of seropositivity, indicating that there was not endemic circulation of MERS‐CoV during the sampling period as in endemic regions, older camels have higher levels of seropositivity. There was no difference in the probability of seropositivity between males and females, similar to the majority of studies (Dighe et al., 2019). However, studies in Kenya did find significant differences where females had higher rates of seroprevalence (Munyua et al., 2017), while male camels in Egypt and KSA had higher seroprevalence compared with female camels (M. A. Ali et al., 2017; Kasem et al., 2018).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Younger camels in Kazakhstan had a higher probability of seropositivity, indicating that there was not endemic circulation of MERS‐CoV during the sampling period as in endemic regions, older camels have higher levels of seropositivity. There was no difference in the probability of seropositivity between males and females, similar to the majority of studies (Dighe et al., 2019). However, studies in Kenya did find significant differences where females had higher rates of seroprevalence (Munyua et al., 2017), while male camels in Egypt and KSA had higher seroprevalence compared with female camels (M. A. Ali et al., 2017; Kasem et al., 2018).…”
Section: Discussionsupporting
confidence: 89%
“…We found that seroprevalence in Kazakhstan (0.35%) was substantially lower compared with any other region (Dighe et al., 2019). The lowest prior detected seroprevalence was in the Canary Islands (4% from 170 camels sampled) and in Mongolia (9.4% from 180 camels) (Bold et al., 2020; Gutiérrez et al., 2015).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation